Psychometric Validation of the German Version of the Rapid Assessment of Physical Activity (RAPA): A Secondary Analysis of Cross‐Sectional Survey Data - Hannah McGowan; Rik Crutzen; Tari Topolski; Stefan Tino Kulnik (Health Science Reports)
Abstract Background and Aims Regular physical activity holds numerous health benefits for older people, yet the majority of older people do not meet the World Health Organization's physical activity recommendations. Brief physical activity screening tools can support healthcare professionals in identifying patients who would benefit from physical activity promotion and counselling. The Rapid Assessment of Physical Activity (RAPA) questionnaire is a validated brief physical activity screening tool designed for clinical practice. Methods We conducted a psychometric validation of a new German translation of the RAPA by performing a secondary analysis of survey data from 234 former cardiac rehabilitation patients (mean [SD] age 69 ± 11 years, 23% female) in Austria. For psychometric validation, we used the following survey measures: the new German version of the RAPA, two customized questions about physical activity behavior, one customized question about perceived health self‐management, and the German version of the EuroQol health‐related quality of life questionnaire. We performed Spearman's correlations to assess the relationship between the German RAPA and the other measures (i.e., physical activity behavior, self‐management of health and health‐related quality of life). Results Aerobic physical activity level according to the RAPA correlated significantly with weekly frequency (Spearman's rho = 0.31, 95% CI [0.18, 0.43], p < .001) and volume of PA (rho = 0.34, 95% CI [0.21, 0.45], p < .001), as well as perceived health self‐management and five out of six dimensions of the EuroQol questionnaire. Conclusion Our data demonstrate convergent validity and contribute to the psychometric validation of the new German version of the RAPA. These initial findings lend themselves to future dedicated psychometric validation studies of the German RAPA (against gold‐standard physical activity questionnaires or direct physical activity measures) to further explore the potential of this tool for use in German‐speaking geriatrics healthcare.